POSITIVE CORRELATION BETWEEN PESTICIDE COMBINATION EXPOSURE RISK STRATIFICATION AND 8-OHDG LEVELS AS A DNA DAMAGE BIOMARKER IN FARMERS - Sulihah, Nurfaizah Titisari; Putri, Elvia Rahmi Marga (Buletin Veteriner Udayana, 2025)
Continuous exposure to pesticide mixtures has a synergistic effect on inducing oxidative stress and DNA damage. One sensitive biomarker of oxidative DNA damage is 8-hydroxy-2'-deoxyguanosine (8-OHdG). This study aimed to analyze the correlation between stratified risk levels of combined pesticide exposure and urinary 8-OHdG concentrations. A cross-sectional design was employed, with pesticide exposure risk assessed through structured interviews and a semi-quantitative scoring method based on usage patterns. Urinary 8-OHdG levels were measured using ELISA. Results demonstrated a moderate positive correlation between combined pesticide exposure risk stratification and 8-OHdG levels (p<0.05), indicating that higher exposure risk corresponds to increased DNA damage. These findings highlight the need for systematic pesticide exposure evaluation and preventive interventions to safeguard farmers' health. Further longitudinal studies are recommended to establish causal relationships between combined pesticide exposure and DNA damage biomarkers, while accounting for potential confounders such as individual metabolic differences and protective measures.